Self Esteem Moderation on Job Satisfaction and Nurse Performance - Dyah, Lembah Andriani Sulistyaning; Irawanto, Dodi W.; Rohman, Fatchur (International Journal of Psychosocial Rehabilitation, 2020)
Hospital is an integral part of the health service system with various types of services, successfull of service and human resource satisfaction. The purpose of this study was to analyze the effect of self esteem as a moderating relationship of job satisfaction on nurse performance. This research is an explanatory survey research with cross sectional approach to nurses in the field of human resources. The research approach is quantitative with the unit of research analysis is the nurse of the mother and child hospital. The sample size of the study were 295 respondents, with a sampling technique using proportional random sampling and the Slovin formula. Data analysis techniques using the Structural Equation Model with PLS Warp analysis tools. The APC, ARS and AARS value were 0.236, 0.244 and 0.337 with a significance